An Empirical Analysis of Career Choice Factors Among Accountants, Attorneys, Engineers, and Physicians*. - Rosen, L. S.; Paolillo, Joseph G. P.; Estes, Ralph W. (The Accounting Review, 1982)
Abstract ABSTRACT: Several studies have identified and reported various factors influencing career-choice decisions of accountants; but none has been reported that systematically relates career-choice factors of accountants with those of other professionals. To provide data for comparisons, ratings of career-choice factors were obtained from accountants, attorneys, engineers, and physicians. A multiple discriminant analysis of these data reveals distinctive differences in career-choice and motivating factors among the four professions.